Special issue Intro: housing estates in the era of marketization – governance practices and urban planning - Kadri Leetmaa; Matthias Bernt (Journal of Housing and the Built Environment, 2022)
This paper introduces a Special Issue of the Journal of Housing and the Built Environment entitled “Housing estates in the era of marketization – governance practices and urban development”. The issue includes 10 European case studies on how marketization has impacted large housing estates (LHEs) across Europe. The collection includes novel contributions from well-studied countries like France or the United Kingdom, cases from Scandinavia and Mediterranean countries, as well as articles from post-socialist cities where the majority of LHEs are situated, and as such presents the diversity of experiences that has emerged in housing estates across Europe in the last two decades. Since the global turn towards neoliberal governance regimes at the end of the 20th century the commodification of housing, accompanied by the financialization of real estate, has not left any housing markets or market segments untouched. All articles focus on the interconnections between problems found in the development of housing estates and the processes of privatization and marketization. We aim to address two main research gaps: (1) we demonstrate that marketization and financialization are preconditions for the development of contemporary housing, incl. housing estate neighborhoods, and (2) we address the need for an up-to-date pan-European overview on contemporary urban governance and planning practices related to LHEs.
Keywords: 690